Studi Karakterisasi Morfologi Asteroidea di Pesisir Pantai Gili Gede Kabupaten Lombok Barat - Khalid, Ahmad Maulidin; Primawati, Sri Nopita; Nofisulastri, Nofisulastri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
Asteroidea is one of the fauna diversity in the Gili Gede area which plays an important role in maintaining the coastal ecosystem. This study aims to provide information on the morphological characterization of Asteroidea on the coast of Gili Gede which is packaged in the form of a practical assistance book for Invertebrate Systematics. The subject of this research is Asteroidea from Phylum Echinoderms. The object of this research is limited to studies on morphological characterization studies of Asteroidea. This is a descriptive exploratory research and used the cruise method by exploring the coastal area of ​​Gili Gede at a predetermined point based on habitat. Data collection techniques are observation and documentation. The measured microclimate parameters (salinity, temperature and humidity). Sampling was carried out in Gili Gede and morphological identification at the Biology Laboratory, Faculty of Applied Science and Engineering, Mandalika University of Education. Based on the identification results, the identified asteroids were Protoreaster nodosus (6 individuals), Linckia laevigata (19 individuals) and Echinaster luzonicus (3 individuals). Protoreaster nodosus and Echinaster luzonicus were found in seagrass habitats while Linckia lavigata were found in sandy substrate habitats and coral reefs. Based on the morphological identification observed (color, body circumference, arm length, madreporite, central canal circumference and spicules). It was found that Protoreaster nodosus had white and black color on the spicules and the ends of the arms, massive body circumference; Linckia laevigata is blue in color and non-massive in circumference; Echinaster luzonicus is black on the dorsal and orange on the ventral side with a non-massive body circumference; There is one madreporite in each specimen. Based on the results of the validation of the assistance book, it shows that it is very valid (obtaining a score of 85) and is suitable for use by students as a source (reference), especially the types of Protoreaster nodosus, Linckia laevigata, Echinaster luzonicus.